Learning Model for Natural Disaster Mitigation Based on Local Wisdom - Arif, Arifuddin M (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The geographical situation of Palu City is rich in local culture and, at the same time, vulnerable to natural disasters. Learning with an insight into natural disaster mitigation based on local wisdom in Junior High Schools (SMP) in Palu City is important. This research aims to explain a learning model with an insight into natural disaster mitigation based on local wisdom in Palu City Junior High Schools (SMP). This research is a type of descriptive qualitative research. The source of research data is learning documents, and the subjects of this research are students and teachers at five junior high schools in Palu City. Data collection techniques were carried out using documentation, observation, and interviews. Data analysis techniques are done by data reduction, classification, and verification. The research results found that the learning model for natural disaster mitigation based on local wisdom was implemented through intracurricular and extracurricular learning activities. Extracurricular activities are taught with a practical preparedness approach in OSIS activities, Scouts, Youth Red Cross (PMR), etc. Intracurricular learning is taught with an integrated approach to natural disaster mitigation material based on local wisdom in Indonesian Language, Natural Sciences, Social Sciences, Civics, and Arts and Culture.